Tracing the emergence of modelling routines during model-eliciting activities. Issue 6 (3rd July 2023) - Shahbari, Juhaina Awawdeh; Tabach, Michal
Abstract : Engagement in complex, challenging and multifaceted model-eliciting activities is considered helpful for preparing learners for everyday life. The current study seeks to trace the evolution of modelling routines during two model-eliciting activities. To identify how these routines emerged and evolved, we video-recorded a group of five prospective teachers as they worked on two model-eliciting activities. We then transcribed the recordings and analysed the prospective teachers' discussion using the lens of learning as routinization. Specifically, in the participants' work on the two model-eliciting activities, we identified three routines that emerged and evolved during their discussion. The main routine focused on integrating all the components provided to create a model. The other routines entailed assigning values to numerical and qualitative data.